2000
DOI: 10.1016/s0926-860x(99)00320-8
|View full text |Cite
|
Sign up to set email alerts
|

The metal–support interaction in Pt/Y zeolite: evidence for a shift in energy of metal d-valence orbitals by Pt–H shape resonance and atomic XAFS spectroscopy

Abstract: The turnover frequency (TOF) for conversion of neo-pentane was determined for Pt in Y zeolite with different numbers of protons and La +3 ions, different Si/Al ratios and with non-framework Al being present. Comparing Pt/NaY to Pt/H-NaY and Pt/K-USY with Pt/H-USY, respectively, shows an increase in the ln (TOF) which is proportional to the number of protons. Compared to NaY, the TOF of Pt in non-acidic NaLaY zeolite is about 25 times higher, which indicates also a strong influence on the charge of the cations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 52 publications
7
71
0
Order By: Relevance
“…[13]. The present measurement data supports that Pt has metallic characteristics, which is agreed well with published results by Koningsberger et al [19,20].…”
Section: En-situ Exafs Measurement For 5 Wt% Pt Loading On Zeolite Casupporting
confidence: 93%
“…[13]. The present measurement data supports that Pt has metallic characteristics, which is agreed well with published results by Koningsberger et al [19,20].…”
Section: En-situ Exafs Measurement For 5 Wt% Pt Loading On Zeolite Casupporting
confidence: 93%
“…Two possible pathways either the surface mobility of adsorbed species or hydrogen adatoms/H + ion may spill over through zeolite framework or on electrode surface [13] in which hydrogen ions (H + ) were able to form OH group with carbon/zeolite acidic surface oxides. The hydrogen spillover on Pt and zeolite acidic sites has also been studied in gas phase [18], in which an anti-bonding state of Pt-H interaction relating to the electronic properties of the catalytic active sites has been observed [4]. This finding can also be used to explain the hydrogen spillover between Pt electrode and solution in electrochemical environment.…”
Section: The Cyclic Voltammetry (Cv) Measurementmentioning
confidence: 96%
“…Nevertheless, the surface oxygen groups, which form the anchoring sites of metallic precursors and metals, are well-known in determining the catalyst supporting material properties [3]. Koningsberger et al [4] has investigated the influence of oxygen atom charge transfer on zeolite using the extended X-Ray adsorption Fine Structure (EXAFS). The increasing of electronegativity nearby the support oxygen atoms was found to increase zeolite alkalinity.…”
Section: Introductionmentioning
confidence: 99%
“…Tauster et al (1978 introduced the concept of strong metal support interaction (SMSI) and observed that some of the metal particles from Group VIII supported on TiO 2 and other reducible oxides lose their chemisorptive properties towards H 2 and CO, when they are reduced at temperature higher than 773 K. Besides, it has been shown that the electron transfer from the oxygen atom present on the support to the metal particle can enhance the electron density and hence the catalytic activity (Triantafillou et al 1995, Watwe et al 1998. In addition, a model based on a study made by extended X-ray absorption spectroscopy (EXAFS), X-ray photoelectron spectroscopy (XPS) and fourier transform infra-red spectroscopy (FTIR) has shown that due to metal-support interaction, a change in the energy position of the metal valence orbital takes place, a factor which affect the catalytic activity (Koningsberger et al 2000. Besides, the charge transfer process between the metal particles and the support can cause significant modification in their catalytic properties.…”
Section: Introductionmentioning
confidence: 99%